CONSPIRACY CRIME IN DRUG OFFENSES: DECISION STUDY NUMBER 277/PID.SUS/2022/PN.MJK - Mas'oed, Wahyu Bagus Putra; Rijadi, Prof. Dr. Prasetijo (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2024)
Drug-related conspiracy is an act committed by some individuals who cooperate or concur to conduct, assist, or support drug-related activities. These activities can include ordering, encouraging, facilitating, consulting, or becoming a member of a drug syndicate. All of this is regulated in Law No. 35/2009 on Drugs. This research aims to find out about the legal application by judges in the Mojokerto District Court and Surabaya High Court in drug conspiracy cases. The research method used is the normative method, which examines each element of the drug-related crime of class I methamphetamine. The results showed that the Mojokerto District Court and Surabaya High Court imposed sentences in accordance with Article 114 Paragraph (1) in appropriate with Article 132 Paragraph (1) of the Law No. 35/2009 on drugs. The conclusion of this research emphasizes the need for more assertive and comprehensive law enforcement in handling cases of drug-related criminal conspiracy. Recommendations are also provided to integrate efforts between law enforcement authorities and intensify preventive efforts through education and socialization of the dangers of narcotics.